Loeselia rzedowskii, sp. nov. (Polemoniaceae), and Rhynchospora jaliscensis, sp. nov. (Cyperaceae), from Jalisco, México - McVaugh, Rogers (Instituto de Ecología, A.C., 1990)
Loeselia rzedowskii, a new shrubby spedes with the habit of L. mexicana but with cream-yellow flowers, is described from Bolaños, Jalisco, and the nearby Sierra de los Huicholes, and Rhynchospora jaliscensis, with almost undivided style, thus referable to Kükenthal’s subgenus Haplostyleae, is describedas new from four localities in the mountains of Jalisco.